Better source memory for remembered to-be-forgotten items than for remembered to-be-remembered items - Ott, Vincent; Höhs, Johanna; Rummel, Jan (Journal of experimental psychology. Learning, memory, and cognition, 2024)
When participants study items one-by-one and are directed to either remember or forget the respective item directly after its presentation, retention of to-be-forgotten items is regularly worse than of to-be-remembered items. We tested whether this directed forgetting effect which is regularly observed for item memory generalizes to source memory. In three experiments, participants studied items in two different source colors (N = 101) or at two different source locations (N = 64; N = 81). Sources were manipulated orthogonally to item type (remember vs. forget). At test, we asked participants to recognize all studied items and also to identify their source. We used a multinomial processing tree model to disentangle item memory, source memory, and guessing. In all three experiments, we replicated the directed forgetting effect in item memory. Source memory for to-be-forgotten items that were recognized despite the intention to forget, however, tended to be even better than source memory for to-be-remembered items that were recognized. These results suggest that the directed forgetting effect does not simply translate from item to source memory. Rather source memory seems to be disproportionally increased in to-be-forgotten items that are remembered. (PsycInfo Database Record (c) 2024 APA, all rights reserved)